2006
DOI: 10.1056/nejmoa051303
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Angioplasty versus Implantation of Nitinol Stents in the Superficial Femoral Artery

Abstract: In the intermediate term, treatment of superficial-femoral-artery disease by primary implantation of a self-expanding nitinol stent yielded results that were superior to those with the currently recommended approach of balloon angioplasty with optional secondary stenting. (ClinicalTrials.gov number, NCT00281060.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
552
4
23

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,063 publications
(620 citation statements)
references
References 21 publications
14
552
4
23
Order By: Relevance
“…To date, there remains no clear-cut de facto gold therapy for endovascular applications in the lower limb with the best outcomes that we can apply to most if not all our patients who present with symptomatic lower limb disease (Table). Current data from numerous trials at various lengths of outcome duration (ranging from 12 to 60 months) [2][3][4][5][6][7][8][9][10][11][12][13] have shown that there remains a consistent but steady decline in primary patency with all devices over time. There has been a robust interest in what should be the default therapy for lower extremity disease.…”
mentioning
confidence: 99%
“…To date, there remains no clear-cut de facto gold therapy for endovascular applications in the lower limb with the best outcomes that we can apply to most if not all our patients who present with symptomatic lower limb disease (Table). Current data from numerous trials at various lengths of outcome duration (ranging from 12 to 60 months) [2][3][4][5][6][7][8][9][10][11][12][13] have shown that there remains a consistent but steady decline in primary patency with all devices over time. There has been a robust interest in what should be the default therapy for lower extremity disease.…”
mentioning
confidence: 99%
“…23,25,26 longer lesions show more frequent restenosis (≈50%) than shorter lesions. 26,52 There is no definitive treatment for ISR.…”
Section: Bare Metal Stents: Proven Liabilitiesmentioning
confidence: 98%
“…21 Remarkably, after >40 years, PTA remains the standard of reference for all percutaneous technologies. [22][23][24][25][26][27][28][29][30][31] The appeal of endovascular therapy was obvious. Conscious sedation and local anesthesia completely sidestepped the complexity, risk, and expense of general anesthesia.…”
Section: The Sweet Spot: Endovascular Therapymentioning
confidence: 99%
See 2 more Smart Citations